Pain interference and depressive symptoms in communicative people with Alzheimer’s disease: a pilot study - Wang, Jinjiao (Aging Ment Health, 2017)
OBJECTIVES: To examine pain interference in verbally communicative older adults with mild to moderate Alzheimer’s disease (AD) and to examine the association of pain interference with cognitive function and depressive symptoms. METHOD: For this pilot study, we used a cross-sectional design to examine pain interference (Brief Pain Inventory-Short Form), cognitive function (Mini-Mental State Exam), and depressive symptoms (15-item Geriatric Depression Scale) in 52 older (≥65) communicative adults with AD who reported being free from chronic pain requiring daily analgesics. RESULTS: Pain was reported to interfere with general activity (13.5%), mood (13.5%), walking ability (13.5%), normal work (11.5%), enjoyment of life (11.5%), relationships with other people (9.6%), and sleep (9.6%). Pain interference was significantly positively correlated with both cognitive function (r(s) = 0.46, p = 0.001) and depressive symptomology (r(s) = 0.45, p = 0.001), indicating that greater reported pain interference was associated with better cognitive function and more depressive symptoms. CONCLUSION: Among older people with AD who report being free from chronic pain requiring daily analgesics, 2 in 10 are at risk of pain interference and depressive symptoms. Those with better cognitive function reported more pain interference and depressive symptoms, meaning pain is likely to be under-reported as AD progresses. Clinicians should regularly assess pain interference and depressive symptoms in older persons with AD to identify pain that might be otherwise overlooked.